Neural stem cells respond to stress hormones: distinguishing beneficial from detrimental stress - Koutmani, Yassemi; Karalis, Katia P. (Frontiers in Physiology, 2015)
Neural stem cells, the progenitors of the nervous system, control distinct, position-specific functions and are critically involved in the maintenance of homeostasis in the brain. The responses of these cells to various stressful stimuli are shaped by genetic, epigenetic and environmental factors via mechanisms that are age and developmental stage-dependent and still remain, to a great extent, elusive. Increasing evidence advocates for the beneficial impact of the stress response in various settings, complementing the extensive number of studies on the detrimental effects of stress, particularly in the developing brain. In this review, we discuss suggested mechanisms mediating both the beneficial and detrimental effects of stressors on neural stem cell activity across the lifespan. We focus on the specific effects of secreted factors and we propose neural stem cells as a “sensor”, capable of distinguishing among the different stressors and adapting its functions accordingly. All the above suggest the intriguing hypothesis that neural stem cells are an important part of the adaptive response to stressors via direct and indirect, specific mechanisms.